Pharmacokinetic and Pharmacodynamic Characterisation of an Anti-Mouse TNF Receptor 1 Domain Antibody Formatted for In Vivo Half-Life Extension - Goodall, Laura J.; Ovecka, Milan; Rycroft, Daniel; Friel, Sarah L.; Sanderson, Andrew; Mistry, Prafull; Davies, Marie L.; Stoop, A. Allart (PLOS ONE, 2015)
Tumour Necrosis Factor-α (TNF-α) inhibition has been transformational in the treatment of patients with inflammatory disease, e.g. rheumatoid arthritis. Intriguingly, TNF-α signals through two receptors, TNFR1 and TNFR2, which have been associated with detrimental inflammatory and beneficial immune-regulatory processes, respectively. To investigate if selective TNFR1 inhibition might provide benefits over pan TNF-α inhibition, tools to investigate the potential impact of pharmacological intervention are needed. Receptor-deficient mice have been very insightful, but are not reversible and could distort receptor cross-talk, while inhibitory anti-TNFR1 monoclonal antibodies have a propensity to induce receptor agonism. Therefore, we set out to characterise a monovalent anti-TNFR1 domain antibody (dAb) formatted for in vivo use. The mouse TNFR1 antagonist (DMS5540) is a genetic fusion product of an anti-TNFR1 dAb with an albumin-binding dAb (AlbudAb). It bound mouse TNFR1, but not human TNFR1, and was an antagonist of TNF-α-mediated cytotoxicity in a L929 cell assay. Surprisingly, the dAb did not compete with TNF-α for TNFR1-binding. This was supported by additional data showing the anti-TNFR1 epitope mapped to a single residue in the first domain of TNFR1. Pharmacokinetic studies of DMS5540 in mice over three doses (0.1, 1.0 and 10 mg/kg) confirmed extended in vivo half-life, mediated by the AlbudAb, and demonstrated non-linear clearance of DMS5540. Target engagement was further confirmed by dose-dependent increases in total soluble TNFR1 levels. Functional in vivo activity was demonstrated in a mouse challenge study, where DMS5540 provided dose-dependent inhibition of serum IL-6 increases in response to bolus mouse TNF-α injections. Hence, DMS5540 is a potent mouse TNFR1 antagonist with in vivo pharmacokinetic and pharmacodynamic properties compatible with use in pre-clinical disease models and could provide a useful tool to dissect the individual contributions of TNFR1 and TNFR2 in homeostasis and disease.